Karotenoidi v oljčnem olju - Bešter, Erika (Annales. Series historia naturalis, 2007)
The pigments profile of virgin olive oil is determined by the pigments initially present in the fruits and their derivatives formed during the extraction process. The presence of other carotenoids or chlorophyll pigments at levels other than that associated with the extraction process indicate that oil has been adulterated or the extraction process was incorrect. The yellow pigments in olive oil are carotenoids and the green pigments are chlorophyll pigments. The amount of carotenoids in oil depends on variety, maturation index, treating of olive fruits before extraction, extraction process, and oil treating. Carotenes as well as xantophylls were identified in virgin olive oils. Lutein is usually the predominating compound in the carotenoid fraction of pigments, followed by B-carotene. The rest of carotenoid fraction are minor xantophylls, such as 5,6-epoxides, 5,8-epoxides or furanoids, and xantophyll esters. Cis-isomeres are also formed during the extraction process. The vitamin activity of cis-isomeres is lower as the activity of trans-isomeres. Pigment profile of olive oil is a useful tool for variety classification and authenticity determination. Carotenoids can act as antioxidants or prooxidants. Their antioxidant/prooxidant activity depend on concentration, solvent, and free radicals structure, presence of other antioxidants, metals and oxygen. The antioxidant activity of carotenoids has not been satisfactory explained as yet. There are three possible mechanisms of carotenoids antioxidant activity. Carotenoids are singlet oxygen quenchers and free radical scavengers and they act as light filters. Findings about carotenoids activity in vitro should not be translated to activity in biological systems. Carotenoids are an important part of human diet because of their antioxidant activity and some of them are also provitamins A. Carotenoids probably prevent some diseases, such as cardiovascular diseases and certain cancers, but can in certain circumstances increase the risk of disease.
Keywords: antioksidanti; antioxidant; karotenoidi; kemijska analiza; oljčno olje